Structural analysis of point mutations at the Vaccinia virus A20/D4 interface. Issue 9 (8th September 2016) - Contesto-Richefeu, Céline; Tarbouriech, Nicolas; Brazzolotto, Xavier; Burmeister, Wim P.; Peyrefitte, Christophe N.; Iseni, Frédéric
Abstract : The Vaccinia virus D4/A20 complex is the DNA polymerase cofactor. The heterodimer interface has been analysed using three new crystal structures of the complex in which key residues forming a cation–π interaction have been mutated. Abstract : The Vaccinia virus polymerase holoenzyme is composed of three subunits: E9, the catalytic DNA polymerase subunit; D4, a uracil‐DNA glycosylase; and A20, a protein with no known enzymatic activity. The D4/A20 heterodimer is the DNA polymerase cofactor, the function of which is essential for processive DNA synthesis. The recent crystal structure of D4 bound to the first 50 amino acids of A20 (D4/A201–50 ) revealed the importance of three residues, forming a cation–π interaction at the dimerization interface, for complex formation. These are Arg167 and Pro173 of D4 and Trp43 of A20. Here, the crystal structures of the three mutants D4‐R167A/A201–50, D4‐P173G/A201–50 and D4/A201–50 ‐W43A are presented. The D4/A20 interface of the three structures has been analysed for atomic solvation parameters and cation–π interactions. This study confirms previous biochemical data and also points out the importance for stability of the restrained conformational space of Pro173. Moreover, these new structures will be useful for the design and rational improvement of known molecules targeting the D4/A20 interface.